2021
DOI: 10.1186/s12885-021-08208-6
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of retroperitoneal lymph node status in locally advanced cervical cancer

Abstract: Background The assessment of retroperitoneal lymph node status in patients with locally advanced cervical cancer is still a problem. This study aimed to explore the choice of these assessment methods. Methods Laparoscopic retroperitoneal lymphadenectomy was performed in 96 patients with advanced cervical cancer. The positive rates of lymph node metastasis were analyzed. The values of computed tomography lymph node minimum axial diameter (MAD) and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 22 publications
0
4
0
1
Order By: Relevance
“…For PALNs in cervical cancer, it was reported in the literature that the positive rate of lymph node metastasis in the group with minimum axial diameter ≥1.0 cm (83.33%) was significantly higher than that in the group with 0.5 cm ≤ MAD (minimum axial diameter) < 1.0 cm (26.82%). The cutoff value of the smallest axial diameter in determining lymph node metastasis is 1.0 cm (16). The study also yielded an area under the receiver operating characteristic (ROC) curve for the smallest axial diameter of lymph nodes on CT scan of 0.782 (95% confidence interval [CI] = 0.706–0.859).…”
Section: Resultsmentioning
confidence: 99%
“…For PALNs in cervical cancer, it was reported in the literature that the positive rate of lymph node metastasis in the group with minimum axial diameter ≥1.0 cm (83.33%) was significantly higher than that in the group with 0.5 cm ≤ MAD (minimum axial diameter) < 1.0 cm (26.82%). The cutoff value of the smallest axial diameter in determining lymph node metastasis is 1.0 cm (16). The study also yielded an area under the receiver operating characteristic (ROC) curve for the smallest axial diameter of lymph nodes on CT scan of 0.782 (95% confidence interval [CI] = 0.706–0.859).…”
Section: Resultsmentioning
confidence: 99%
“…Another study showed that maximum axial diameter ≥10 mm on CT and SCC antigen level ≥5.2 ng/mL represent risk factors for lymph node metastases in cervical cancer. 16 The radiographic staging of PLN metastasis is difficult; however, since this area is within the scope of radiotherapy, its impact on prognosis is minimal. Since this study involved a small number of cases, the risks of false-negatives and false-positives were unknown.…”
Section: Discussionmentioning
confidence: 99%
“…In case 6, whose SCC antigen level was low (3.4 ng/mL) despite the large tumor size (60 mm), showed a smallest PLN metastasis size of 8 mm, and a SUVmax of 3.5. Another study showed that maximum axial diameter ≥10 mm on CT and SCC antigen level ≥5.2 ng/mL represent risk factors for lymph node metastases in cervical cancer 16 . The radiographic staging of PLN metastasis is difficult; however, since this area is within the scope of radiotherapy, its impact on prognosis is minimal.…”
Section: Discussionmentioning
confidence: 99%
“…Первый выбор -хирургическая резекция. Парааортальная лимфодиссекция не только полезна для выявления потенциальных метастазов ЛУ у пациенток с раком шейки матки, но также обеспечивает терапевтический эффект [14]. Первоначально операция выполнялась путем лапаротомии, но от нее отказались из-за высокого уровня осложнений (от 10 до 16 %).…”
Section: лечение пациенток с метастазами в Paln (парааортальные лимфо...unclassified